Case studies of waqf governance in selected Muslim-minority countries - Syed Abdul Kader, Sharifah Zubaidah (2016)
Waqf (plural, awqaf) is an Islamic endowment created by a waqif (waqf founder/donor) who dedicates his property in perpetuity for the benefit of specific beneficiaries (waqf khas) or the public (waqf ‘am) for the purpose of reaping rewards accruing even after his death.1 For the majority of Muslims, the purpose of creation of waqf is to get closer to God and for the enhancement of charitable deeds. Once endowed, the waqf property (‘corpus’) is inalienable and cannot be sold or inherited, only the usufruct can be used for the benefit of the beneficiaries or invested for further generation of income including, to maintain and improve the corpus of waqf property itself.2 It is therefore a self-sustaining and dynamic concept that when applied effectively would be able to contribute to economic growth, development, social justice and prosperity of the whole society. The practice of waqf was enjoined by Prophet Muhammad amongst his companions and has been widely practised by Muslims throughout Muslim civilisation. Waqf property can be found all over Muslim countries as well as wherever Muslim communities are located in Muslim minority countries.